Functional neuroanatomy: the locus of human intelligence. - Nachev, P; Mah, Y; Husain, M (2009)
A new study mapping the functional effects of brain lesions has revealed a surprising map of human intelligence, stimulating a re-evaluation of data from purely correlative methods such as functional magnetic resonance imaging.